Analysis Of The Practicality Of Educational Animation Learning Media Based On Linktr.Ee On Explanatory Text Material For 11th Grade Students Of State High School 4 Tanjungpinang For The 2023/2024 Academic Year - Loren Fabio Testy Ariance; Elfitra Legi; Wahyusari Ahada; Malik Abdul; Santy Isnaini Leo; Selvira Lisa; Sarkity Dios; Zhou Shenglan (SHS Web of Conferences)
Learning media actually aims to make it easier to achieve learning goals. However, easy use will increase the function of the learning media. Therefore, this research aims to see the practicality of educational animation learning media using the Linktr.ee platform in explanatory text material for class XI students at SMA Negeri 4 Tanjungpinang for the 2023/2024 academic year. Data was collected through a media practicality questionnaire by students involving 6 students for small groups and 30 students for large groups. Data analysis was carried out using quantitative descriptive methods. The results of this research show that educational animated learning media using the Linktr.ee platform is very good for use in learning with the percentage of trials with students showing an average of 93% with the criteria “very practical” from small groups and an average of 84% with the criteria “very practical” from a large group.